PERANAN APARAT HUKUM DALAM PENANGGULANGAN TERORISME DI INDONESIA - Wahyu, Wahyu (Sekolah Tinggi Hukum Bandung, 2011)
The main and essential purpose of law is to achieve justice. In oder to achieve justice in society, there should be an orde at first. Disorder and chaos can be caused by the terrorism movement. Terrorism movement in Indonesia has alraedy been increasing rapidly, both frequncies and acceleration. It goes without saying that there is a tool of legislation regulating the eradication of terrorism criminal act, namely Act No. 15 year 2003. That Act has been applied and effective since 2003, and after being implemented by the lawÂ enforcement apparatus, especially the Republic of Indonesia State Police, there are still psycological and juridicaltechnical obstacles, so the handling of this terrorism criminal act has not been successful optimally. As the terrorism criminal act is not only a local movement, but also an international network by using high technology, and terrorism movement in Indonesia has a background of islamic fundamental ideology, the government should not only use repressive paradigm and juridical approach, but also psychological and religioussociological approaches.Keywords: law enforcement; terrorism; justice; eradication